1999
DOI: 10.1677/joe.0.1600305
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution and ontogeny of insulin-like growth factors (IGFs) and IGF binding protein messenger RNAs and peptides in developing rat pancreas

Abstract: To determine the role of insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) in the development of the pancreas, and specifically of the islets of Langerhans, we have examined the cellular distribution and developmental changes in the expression of IGFs and IGFBPs in the pancreas of the fetal and neonatal rat between 19·5 days of gestation and postnatal day 28. This represents a period of substantial growth and restructuring of the cell component in islets of this species. IGF-I, IGF-II, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Blocking of endogenous IGF-II with an IGF-II antibody inhibited this protective effect . A decrease in apoptosis in islet cells has also been found in transgenic mice overexpressing IGF-II, giving rise to a marked islet hyperplasia (Petrik et al 1999). Ilieva et al (1999) have recently reported that hamster pancreatic duct epithelium contained IGF-II and that this secretion has an anti-apoptotic effect on B-cells; these results are not in line with ours but raise the question about species dependent differences in IGF-II localization.…”
Section: Discussionmentioning
confidence: 58%
“…Blocking of endogenous IGF-II with an IGF-II antibody inhibited this protective effect . A decrease in apoptosis in islet cells has also been found in transgenic mice overexpressing IGF-II, giving rise to a marked islet hyperplasia (Petrik et al 1999). Ilieva et al (1999) have recently reported that hamster pancreatic duct epithelium contained IGF-II and that this secretion has an anti-apoptotic effect on B-cells; these results are not in line with ours but raise the question about species dependent differences in IGF-II localization.…”
Section: Discussionmentioning
confidence: 58%
“…It is known that IGFs and their binding proteins (IGFBPs) are expressed by islet cells throughout life (Hill et al 1999). In rats, IGF-2 levels are relatively high in fetal and early neonatal period and then they decline sharply toward adulthood, while IGF-1 levels increase progressively with age (Hogg et al 1994, Petrik et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…This effect persists until adulthood ) and can provoke long-lasting consequences related to the plasticity of the endocrine pancreas under situations of increased insulin demand such as aging and pregnancy (Blondeau et al 1999). Accordingly, nutritional insufficiency can alter the timing and amplitude of the ontological events, which trigger the remodeling of endocrine pancreas (Petrik et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the involvement of the IGF family in beta cell development is abundant and based on physiological studies [7] and genetic mouse models [7][8][9] as follows: (1) IGFs are mitogenic for beta cells [7]; (2) IGFs and their binding proteins are produced in fetal and adult pancreata [10]; (3) IGFs act as cell survival factors by inhibiting beta cell apoptosis [7]; (4) IGF2 overexpression in transgenic mice causes islet hyperplasia [11]; and (5) undernourished fetuses with an increased beta cell mass have locally increased pancreatic Igf1 expression [12].…”
mentioning
confidence: 99%